PENYULUHAN PENGETAHUAN IBU HAMIL TENTANG IMUNISASI TETANUS TOXOID DI WILAYAH KERJA PUSKESMAS ASTAPADA KECAMATAN TENGAH TANI KABUPATEN CIREBON - Sofiyati Sofiyati (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2023)
Tetanus is caused by bacteria that enter through an open wound and produce a toxin which then attacks the central nervous system. Sufferers experience muscle spasms followed by difficulty swallowing and even breathing. Tetanus is especially at risk for babies born with the help of traditional birth attendants at home with non-sterile equipment. They are also at risk when unclean tools are used to cut the umbilical cord and traditional ointments or ashes are used to cover the cut wound. One of the efforts to prevent tetanus neonatorum is by giving TT (Tetanus Toxoid) immunization to pregnant women. This TT immunization is expected to reduce the number of tetanus cases in Indonesia, so that the community needs to be provided with information so that their knowledge and attitudes about TT immunization can be implemented especially for pregnant women.